Comparing Seroma Formation at the Deep Inferior Epigastric Perforator, Transverse Musculocutaneous Gracilis, and Superior Gluteal Artery Perforator Flap Donor Sites after Microsurgical Breast Reconstruction - Merchant, Alisha; Speck, Nicole E.; Michalak, Michal; Schaefer, Dirk J.; Farhadi, Jian (Archives of Plastic Surgery, 2022)
Background Seroma formation is the most common donor site complication following autologous breast reconstruction, along with hematoma. Seroma may lead to patient discomfort and may prolong hospital stay or delay adjuvant treatment. The aim of this study was to compare seroma rates between the deep inferior epigastric perforator (DIEP), transverse musculocutaneous gracilis (TMG), and superior gluteal artery perforator (SGAP) donor sites.Methods The authors conducted a retrospective single-center cohort study consisting of chart review of all patients who underwent microsurgical breast reconstruction from April 2018 to June 2020. The primary outcome studied was frequency of seroma formation at the different donor sites. The secondary outcome evaluated potential prognostic properties associated with seroma formation. Third, the number of donor site seroma evacuations was compared between the three donor sites.Results Overall, 242 breast reconstructions were performed in 189 patients. Demographic data were found statistically comparable between the three flap cohorts, except for body mass index (BMI). Frequency of seroma formation was highest at the SGAP donor site (75.0%), followed by the TMG (65.0%), and DIEP (28.6%) donor sites. No association was found between seroma formation and BMI, age at surgery, smoking status, diabetes mellitus, neoadjuvant chemotherapy, or DIEP laterality. The mean number of seroma evacuations was significantly higher in the SGAP and the TMG group compared with the DIEP group.Conclusion This study provides a single center's experience regarding seroma formation at the donor site after microsurgical breast reconstruction. The observed rate of donor site seroma formation was comparably high, especially in the TMG and SGAP group, necessitating an adaption of the surgical protocol.
Keywords: seroma; mammaplasty; surgical flaps; microsurgery